Effects of brining ingredients and antimicrobials on thermal inactivation of Escherichia coli O157:H7 in a meat model system and control of Listeria monocytogenes in frankfurters - Byelashov, Oleksandr Anatolievich, author; Sofos, John N., advisor (Colorado State University. Libraries, 2009)
Microbial food safety has been one of the most important challenges for the meat industry and regulatory agencies during the last two decades owing to outbreaks by pathogens such as Escherichia coli 0157:H7 and Listeria monocytogenes traced tocontaminated products, and associated with costly product recalls from the market. Among others, E. coli 0157:H7 infections have been associated with undercooked contaminated brine-injected meats. L. monocytogenes is of particular concern in ready-to-eat (RTE) meat and poultry products.

One part of this dissertation evaluated the effect of brining ingredients, as well as existing and novel antimicrobials, on the fate of E. coli 0157:H7 during storage and onits thermal (65°C) inactivation in an inoculated (7 log CFU/g) brine-injected meat (two fat levels) model system. The following compounds, alone or in combinations, were mixed with inoculated ground meat: sodium chloride, sodium tripolyphosphate, sodiumpyrophosphate, potassium lactate, sodium diacetate, lactic acid, acetic acid, citric acid, nisin, pediocin, sodium metasilicate, cetylpyridinium chloride (CPC), and hops beta acids. Overall, findings showed that common brining ingredients, sodium chloride and sodium phosphates, did not affect (P > 0.05) the pathogen during storage and neither protected nor sensitized it to heat. Among tested antimicrobials, CPC was the only antimicrobialt hat reduced (by approximately 1 log-cycle) E. coli 0157:H7 during storage. The effect of fat content on the fate of E. coli 0157:H7 was negligible. Thermal treatment reduced pathogen numbers by 1.5 to 2.5 log-units. CPC-, nisin- and pediocin-treated samples showed an enhanced (P < 0.05) thermal destruction of the bacterium, compared to the sodium chloride plus sodium tripolyphosphate control treatments, while other compounds did not influence thermal inactivation.

Another study examined the effect of lactic acid (LA) dipping solutions on L.monocytogenes numbers on surface-inoculated (4.4 log CFU/cm2) frankfurters, and determined parameters (temperature: 4 to 55°C; LA concentration: 1 to 3%; and exposure time: 15 to 120 sec) achieving 1 and 2 log-unit immediate reductions. These reductions may allow processors to meet regulatory requirements, as it is required that post-lethality treatments must reduce the pathogen by at least 1 log-cycle, while processing plants employing treatments that reduce the pathogen by at least 2 log-cycles should be subject to less frequent microbial sampling and testing. Distilled water, at all temperatures, and LA applied at 4°C reduced pathogen counts by approximately 1 log-cycle. Overall, the magnitude of the antimicrobial effect of LA against L. monocytogenes increased with solution concentration, temperature, and to a lesser extent, by dipping time. A 2-log reduction was obtained by 1% LA applied at 55°C for 60 s or by 3% LA applied at 25°C- for 120 s. A developed prediction equation for L. monocytogenes reduction included significant (P < 0.05) effects of the linear terms of concentration, time, temperature, and interaction of concentration and temperature; other tested parameters (other interactions, quadratic and cubic terms) did not affect (P > 0.05) the reduction within the range of the tested experimental conditions. This equation may help processors to vary parameters (temperature, LA concentration and time) of post-lethality treatments to achieve a 1 or 2 log-unit reduction of L. monocytogenes and to meet regulatory requirements.

Another study evaluated the effect (immediate and during 90-d storage) of LA (5% vol/vol) and sodium lauryl sulfate (SLS; 0.5% wt/vol), sprayed individually or as a mixture (LA/SLS), against L. monocytogenes on surface-inoculated (4.8 log CFU/cm) frankfurters. The LA/SLS was applied before or after inoculation. Spraying with distilled water, LA or SLS after inoculation reduced numbers of L. monocytogenes by 1.3 ± 0.2, 1.8 ± 0.5 and 2.0 ± 0.4 log CFU/cm2, respectively. Reduction by LA/SLS mixture applied after inoculation (2.8 ± 0.2 log CFU/cm2) was higher (P < 0.05) than that achieved by the mixture applied before inoculation (1.8 ± 0.4 log CFU/cm). Further, treatments that contained LA delayed growth and decreased growth rate of the pathogen.

A last study evaluated the fate of L. monocytogenes on surface-inoculated (1.8 log CFU/cm2) frankfurters formulated with or without 1.5% potassium lactate and 0.1% sodium diacetate (PL/SD) and stored under fluctuating conditions. These conditions imitated pre-shipment storage (24 h, 4°C), temperature mishandling during distribution (7 h, 7°C followed by 7 h, 12°C), and storage before purchase (60 d, 4°C; SBP). At 0, 20, 40, and 60 d of SBP, samples were exposed to conditions that followed those encountered during transportation from retail to consumers (3 h, 23°C). Then, vacuum-packages were opened or kept intact at 4 or 7°C for 14 d (SHF). L. monocytogenes numbers were relatively stable on products with PL/SD regardless of storage conditions; but, they increased on samples without PL/SD. In vacuum-packages, during SHF at 4°C, the pathogen grew faster (P < 0.05) on aged frankfurters (20 d of SBP) compared to frankfurters that were fresh (0 d of SBP); a similar trend was seen in opened packages. At 7°C in opened packages growth rates (0.35 ± 0.02 log CFU/cm2/d) were the highest on fresh product. By day-40 of SBP L. monocytogenes reached high levels and grew slowly or stayed constant during SHF.

Overall, the results of the studies reported in this dissertation may be useful in developing storage recommendations and interventions to control L. monocytogenes on frankfurters, as well as in developing and improving brining recipes to control E. coli 0157:H7 in moisture-enhanced meat products. Further, these data may be useful in pathogen risk assessments for RTE and moisture-enhanced meat products.
Keywords: antimicrobials; brining; Escherichia coli O157:H7; frankfurters; Listeria monocytogenes; thermal inactivation; microbiology; public health; food science